KAJIAN EFIKASI DIRI IBU MENYUSUI DALAM MEMBERIKAN ASI EKSKLUSIF STUDI DIWILAYAH KERJA PUSKESMAS BANGKALAN - Dwi Wahyuning Tyas (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
The main food for babies aged 0-6 months according to experts is Breast milk (ASI), breastfeeding for infants aged 0-6 months recommended for 6 months without any additional feeding, based on a preliminary study in the working area of the health center there are 60% the mother did not succeed in giving exclusive breastfeeding to the baby for 6 months. One of the reasons for the mother not succeeding in giving exclusive breastfeeding revealed the reason that the mother felt uncertain about giving breast milk to her baby, the mother assumed that the milk provided did not adequately meet the needs of her baby, so the baby often cried and assumed that the baby was crying hungry. Confidence Self-ability to what extent a person can complete a task is known as self-efficacy. The design of this study was descriptive, respondents used mothers of infants aged 7-10 months at community health center in Bangkalan. The data collection tool uses a questionnaire. Based on the results of the study, most respondents had less self-efficacy of 55.6%, almost half were <20 years old as many as 37.1%, most of them were multiparas, as many as 64.8%, almost half took secondary education as many as 42, 6%, most have breastfeeding experience which is as much as 74.1%, most of the respondents did not succeed in giving exclusive breastfeeding which is as much as 72.2%. Efforts are needed to provide information about exclusive breastfeeding both through health education and sharing experiences about success and failure in giving exclusive breastfeeding to improve one's self-efficacy